INTERTWINING URBAN-NATURE: SENAYAN PARK WETLAND CENTER - Natasadiya, Trevina
The attachment of urban residents to the natural life around them is getting further and further away. Within a short period of time, humans have experienced a transition from a life that was mostly spent outside to a very different life that was mostly spent inside buildings and in urban contexts. The three main problems discussed are urban residents’ high level of stress, built environment including its architecture system is usually separated from natural processes that is happening around it, and the last one is the loss of flora and fauna which will result in decreased biodiversity and ecosystem imbalance. The absence of nature in cities can lead to the main problem faced by urban residents, The absence of chances for urban residents to interact with nature may lead to ‘extinction of experience’ and could affect natural damage beyond cities.